2012
DOI: 10.1016/j.heares.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Marker entry into vestibular perilymph via the stapes following applications to the round window niche of guinea pigs

Abstract: It has been widely believed that drug entry from the middle ear into perilymph occurs primarily via the round window (RW) membrane. Entry into scala vestibuli (SV) was thought to be dominated by local, inter-scala communication between scala tympani (ST) and SV through permeable tissues such as the spiral ligament. In the present study, the distribution of the ionic marker trimethylphenylammonium (TMPA) was compared following intracochlear injections or applications to the RW niche, with or without occlusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 30 publications
3
50
0
1
Order By: Relevance
“…Different drugs had different results [15,16] . It was reported that application of gentamicin to oval window caused more vestibulotoxicity and hearing loss in Gunea pigs [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different drugs had different results [15,16] . It was reported that application of gentamicin to oval window caused more vestibulotoxicity and hearing loss in Gunea pigs [17] .…”
Section: Discussionmentioning
confidence: 99%
“…King et al [16] estimated that the rate of gadolinium absorption in the region of stapes was more than 90%. Salt et al [15] showed that trimethylphenylammonium (TMPA) marker was absorbed at a rate of 65% from the round window. Placing gentamicin to the oval window caused a mean increase of 17±22.6 in the caloric weakness.…”
Section: Discussionmentioning
confidence: 99%
“…TTX (250 ng/ml in artificial perilymph) was injected from a pipette sealed into a fenestra at the cochlear apex. The composition of artificial perilymph, in millimolar, was NaCl (127.5), KCl (3.5), NaHCO 3 (25), CaCl 2 (1.3), MgCl 2 (1.2), NaH2PO 4 (0.75), and glucose (11) (Salt et al 2012). Control experiments utilized artificial perilymph without TTX.…”
Section: Apical Injection Of Tetrodotoxinmentioning
confidence: 99%
“…When a drug reaches the inner ear from the middle ear cavity, it must pass the round window membrane or oval window (Zou et al, 2010;Pyykko et al, 2011). Although there is some controversy regarding which is the dominant route for the inner ear, the round window membrane seems to be superior (Salt et al, 2012). Factors affecting the permeability of a drug through the round window membrane include the size, configuration, concentration, lipid-solubility, and electrical charge of the drug itself, and the thickness of the round window membrane (Goycoolea, 2001).…”
Section: Number Of Particles In Lateral Wall Modiolusmentioning
confidence: 99%